Pengaruh Penggunaan Gadget terhasap Akhlak Peserta Didik Kelas V MIs Hidayatusshibyan - Yulia Rahman; Edy Edy (STIT Sirojul Falah Bogor, 2022)
Gadget users in this modern era are not only parents and teenagers, most elementary school children can already operate gadgets as entertainment media that make them addicted so that the consequences of addiction can change children's morals to be bad. The purpose of this study was to determine the effect of using gadgets on the morals of the fifth grade students of MIS Hidayatusshibyan.This type of research is quantitative research. The results showed that there was a negative influence on the use of gadgets on the morals of fifth grade students at MIS Hidayatusshibyan. This is evidenced by the results of the tabulation of the calculation of the questionnaire which is included in the fairly strong category. This correlation value can be seen from the results of the interpretation of the rxy value of 0.535 which is located between 0.40 to 0.599 with a fairly strong correlation interpretation, the